On-farm validation of management technology for seed and soil borne safflower diseases: On-farm validation of management technology for seed and soil borne safflower diseases - S V PAWAR,; S B GHUGE,; P O BHUTADA, (Journal of Oilseeds Research, 2020)
On farm validation for seed and soil borne safflower disease management technology was conducted at Parbhani to evaluate the Trichoderma strain (Th4d)) as seed dresser compared with farmers’ practice. The seed treatments, Trichoderma harzianum Th4d SC @ 2 ml/kg and Trichoderma harzianum Th4d WP @ 10 g/kg were most effective with significantly least incidence of 5.3% of seed/soil borne disease as compared to farmers’ practice where the disease incidence was 11.3%. The treatment Trichoderma harzianum Th4d SC @ 2 ml/kg and Trichoderma harzianum Th4d WP @ 10 g/kg also recorded highest seed yield (1034 and 1055 kg/ha) followed by Carbendazim+Mancozeb (SAFF) @ 0.2% (977 kg/ha). The cost-benefit analysis showed that the seed treatment with Trichoderma harzianum Th4d WP @ 10 g/kg recorded the highest net monetary returns of `16,700/-.